Relationship of Breastfeeding Techniques with Nipple Event on Breast Milk at Post Partum Mother in PuskesmasPeukanBada of Aceh Besar District - Lisa, Ulfa Farrah (Universitas Ubudiyah Indonesia, 2017)
The failure of exclusive breastfeeding to the baby can be caused by problems faced during breastfeeding, one of which is a scratched nipple. The episodes of scratched nipples can be resolved by correct breastfeeding techniques, therefore skills in breastfeeding are required. Based on data obtained at Peukan Bada Aceh Besar Public Health Center got data from October 2016 that observation amounted to 10 people found 7 out of 10 women had nipple blisters. The purpose of this research is to know the relation of skill of breastfeeding technique with the occurrence of nipple blisters on post partum mothers in the work area of Peukan Bada Public Health Center of Regency of Aceh Besar in 2016. This research is analytic with cross sectional approach, research conducted on November 15 until December 28 2015, population of all post-partum mothers 0-40 days in Peukan Bada Aceh Besar Community Health Center, sampling using total sampling technique amounted to 48 people, data analysis using chi square test. The incidence of scratch nipple was more encountered in the respondents with less skill that is 86% compared with the respondents whose good skill is 20%. After the chi-square statistic test was obtained p-value 0,001 (P <0,05), showed a significant relationship between skill of breastfeeding technique with the happening of nipple blisters. There is a demonstration effectiveness of breastfeeding techniques on the incidence of scuffed nipples and the effective demonstration of breastfeeding techniques on breastfeeding skills. It is expected that research sites can be input for health institutions, especially health workers in the Peukan Bada Community Health Center to plan and improve post-partum breastfeeding techniques.Keywords:Â Breastfeeding Techniques,Â Nipple Event